Biological therapy in the reduction of cardiovascular risk in patients with psoriasis - Andrés Tirado-Sánchez (Revista Médica del Hospital General de México)
Psoriasis is a chronic inflammatory disease that primarily affects the skin, and its complications include a predisposition to atherosclerosis and cardiovascular disease (CVD), with this risk related to the severity of psoriasis. The mechanisms by which psoriasis predisposes to CVD are not clear. They are attributed to persistent chronic inflammation, which is a common factor in both diseases. However, timely recognition of psoriasis and initiation of systemic therapy may improve the prognosis of the disease. The hypothesis that the inflammatory cascade activated in psoriasis contributes to the atherosclerotic process provides a basis for suggesting that anti-inflammatory therapy that ameliorates psoriasis activity would also reduce CVD risk. Biological therapy that inhibits certain proinflammatory cytokines, such as tumor necrosis factor-α, interleukin (IL)-12/23, and IL-17, has a direct effect on the development of psoriasis and, in addition to reducing the risk of developing psoriasis, may improve vascular damage. However, the available information is not entirely conclusive, and further studies are needed to define the true role of these drugs in the prevention and prognosis of CVD in patients with severe forms of psoriasis and with various comorbidities. This review analyzes recent studies that suggest a protective effect of biologic therapies in the risk of CVD in patients with psoriasis.